Enhancement clinic for structural analysis fundamentals / Ir. Dr. Goh Lyn Dee - Goh, Lyn Dee (Unit Penerbitan PKAPP, 2024)
The Enhancement Clinic for Structural Analysis Fundamentals was held on 16th December 2023 (Saturday) at Blok Akademik BKBA, gathering 47 students from the Statics and Dynamics, Indeterminate Structures, and Reinforced Concrete Design classes. Ten early attendees were greeted with welcome gifts, a gesture meant to motivate and encourage active participation throughout the day.